2004
DOI: 10.1128/jcm.42.6.2701-2706.2004
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Prevalence of Active Drug Efflux Mechanism in Various Multidrug-Resistant Klebsiella pneumoniae Strains from Turkey

Abstract: The prevalence of active drug efflux pump and porin alterations was investigated in Turkish nosocomial strains of Klebsiella pneumoniae exhibiting a multidrug-resistant phenotype. MICs of various antibiotics, including quinolones, chloramphenicol, tetracycline, and ␤-lactams, for those strains were determined either with or without the efflux pump inhibitor phenylalanine arginine ␤-naphthylamide (PA␤N). Thirty-nine percent of the strains exhibited a PA␤N-modulated resistance for quinolones, chloramphenicol, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
88
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 30 publications
(71 reference statements)
4
88
0
3
Order By: Relevance
“…a study of Klebsiella pneumoniae strains collected from different patients undergoing treatment indicated that the isolates exhibited modified outermembrane permeability 22 . In most of these isolates, OmpK35, which belongs to the OmpF porin group and has a large channel size, was replaced with OmpK36, which belongs to the OmpC porin group and possesses a smaller channel size.…”
Section: Alterations In Porin Expressionmentioning
confidence: 99%
“…a study of Klebsiella pneumoniae strains collected from different patients undergoing treatment indicated that the isolates exhibited modified outermembrane permeability 22 . In most of these isolates, OmpK35, which belongs to the OmpF porin group and has a large channel size, was replaced with OmpK36, which belongs to the OmpC porin group and possesses a smaller channel size.…”
Section: Alterations In Porin Expressionmentioning
confidence: 99%
“…The test results confirmed the existence of a PA␤N-susceptible efflux mechanism in all E. aerogenes and many K. pneumoniae strains, with marked decreases in the MICs of fluoroquinolones and chloramphenicol in the presence of PA␤N (Table 1). Efflux pump activity was identified when the PA␤N addition induced a threefold decrease in the MIC of an antibiotic molecule (4,9). For the two fluoroquinolones, the PA␤N addition had better efficiency in decreasing the MICs of sparfloxacin than those of norfloxacin.…”
mentioning
confidence: 99%
“…We used the twofold broth dilution method with Mueller-Hinton broth according to the CLSI guidelines: the tests were carried out with or without the broad-spectrum efflux pump inhibitor (EPI) phenylalanine arginine ␤-naphthylamide (PA␤N). This diamine compound, used at a low concentration (26.3 mg/liter), can increase the activities of chloramphenicol, tetracycline, norfloxacin, and sparfloxacin against various enterobacterial isolates which overproduce efflux pumps such AcrAB-TolC (4,9,16). The test results confirmed the existence of a PA␤N-susceptible efflux mechanism in all E. aerogenes and many K. pneumoniae strains, with marked decreases in the MICs of fluoroquinolones and chloramphenicol in the presence of PA␤N (Table 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations